2016
DOI: 10.1371/journal.pone.0165950
|View full text |Cite
|
Sign up to set email alerts
|

Benznidazole Use among Patients with Chronic Chagas' Cardiomyopathy in an Endemic Region of Brazil

Abstract: Chagas disease (CD) is a neglected tropical disease that affects individuals in almost every country in Latin America. There are two available drugs with antiparasitic profiles; however, only benznidazole (BZN) has been approved for commercialization in Brazil. The usefulness of prescribing BZN for patients with chronic Chagas cardiomyopathy (CCC) is controversial. There are no studies in the literature describing the extent of BZN use at this stage or the profile of patients using this drug. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
6
0
7
Order By: Relevance
“…As variáveis do histórico médico que apresentaram associação com o óbito foram presença de hipertensão arterial, não uso prévio de BZN, ser portador de marca-passo, classe funcional com limitação e NT-proBNP alterado. Tais eventos estão relacionados ao possível agravamento da DC e ao dano cardíaco 32 , conforme já discutido. A classe funcional categoriza a extensão da insuficiência cardíaca, sendo que indivíduos sem limitação não apresentam restrição funcional em suas atividades rotineiras 33 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…As variáveis do histórico médico que apresentaram associação com o óbito foram presença de hipertensão arterial, não uso prévio de BZN, ser portador de marca-passo, classe funcional com limitação e NT-proBNP alterado. Tais eventos estão relacionados ao possível agravamento da DC e ao dano cardíaco 32 , conforme já discutido. A classe funcional categoriza a extensão da insuficiência cardíaca, sendo que indivíduos sem limitação não apresentam restrição funcional em suas atividades rotineiras 33 .…”
Section: Discussionunclassified
“…A classe funcional categoriza a extensão da insuficiência cardíaca, sendo que indivíduos sem limitação não apresentam restrição funcional em suas atividades rotineiras 33 . A associação da classe funcional com o pior prognóstico da DC também já foi reconhecida 32 . O BZN é o único medicamento antiparasitário que age no T. cruzi, permitido para comercialização no Brasil 34 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Not using BZN also increased the probability of experiencing cardiovascular events, but the p value observed in this association was borderline (p = 0.057) and this result needs to be analyzed with caution. Previous use of this drug is still considered reduced among patients with CD in Brazilian endemic regions (27%) [15]. Previous studies have found that BZN use has been associated with a significant reduction in parasitemia [32], lower prevalence of severe cardiomyopathy markers, and lower mortality [48].…”
Section: Discussionmentioning
confidence: 99%
“…The SaMi-Trop methodology has been presented in detail in previous publications [14,15]. The main points of the methodology of this cohort are described in the following paragraphs.…”
Section: Individual Datamentioning
confidence: 99%